COHERENT VORTEX STRUCTURES INSIDE THE CROSS-STREAMLINED OVAL DIMPLE - Воскобійник, В.А.; Воскобійник, А.В. (Science-based technologies, 2014)
Results of experimental researches of the vortex structure inside the cross-streamlined oval dimple on a hydraulically smooth flat surface are presented. By means of flow visualization by the contrasting dyes and water soluble coatings the features of forming and evolution of coherent large-scale and small-scale vortex structures are determined inside the dimple. For small Reynolds numbers responding by laminar flow coherent vortices are not generated inside the oval dimple. For the Reynolds numbers about 10000 the cellular quasistable large-scale vortex structures are formed inside the dimple, which are ejected into the boundary layer above an aft dimple wall. For the developed turbulent flow a spindle vortex structure is generated in the dimple which is pressed to the front bottom part of the dimple.